Influência das metaloproteinases da matriz extracelular no carcinoma de células escamosas oral: uma revisão de literatura - Andrade, Géssica de Oliveira (2018)
Oral squamous cell carcinoma (CCEO) is one of the most common worldwide, accounting for an estimated 1-2% of deaths caused by cancer. In CCEO, matrix metalloproteinases (MMPs) are associated with extracellular matrix degradation (ECM). The objective of the present study is to perform a literature review on the main MMPs and their association to the CCEO. The survey was conducted in the PubMed database between February and August 2018. The MMP-2 and -9 merit notoriety for collaborating in the invasion and metastasis processes. These enzymes are suggested as a prognostic factor, mainly detecting the invasion capacity of the lesions.